Innovation of Healthy Drinks Products from Local Ingredients for the Economic Empowerment of Roay Lestari Women Farmers Group in Tasikmalaya - Mutmainah, Lu'liyatul; Andani, Listia; Fikrinnisa, Rizka; Kurniawan, Akbar Rizqi (Universitas Muhammadiyah Palembang, 2026)
Women Farmers Groups play a strategic role in meeting local food security and empowering women in the agricultural sector. This community service activity aims to empower Kelompok Wanita Tani (KWT-Women Farmers Group) Roay Lestari in Tasikmalaya through innovative healthy beverage products made from local ingredients. This activity is carried out based on an analysis of potential situations that have not been optimally utilized to improve the economic welfare of its members. The main problems faced are limited knowledge about processing agricultural products into value-added products, lack of market access, and low entrepreneurial skills. Through a participatory approach, this activity provides training in making healthy beverages using cold-pressed juice techniques, product packaging assistance, and entrepreneurship training. The results of the activity showed a significant increase in the knowledge and skills of KWT members regarding the processing of healthy beverage products. Three types of healthy drinks, namely green juice, yellow juice, and orange juice without additives, became the best-selling consumer products, as well as two types of herbal drinks, namely lemongrass lemon tea and turmeric tamarind. KWT Roay Lestari has successfully developed innovative health drink products made from local ingredients, including other derivative products such as spiced tea and rhizomes.